Structure of knowledge in the culture of weaving of Thai-Khmer ethnic group / Jutamas Promthong, Malee Kabmala and Wirapong Chansanam - Promthong, Jutamas; Kabmala, Malee; Chansanam, Wirapong (Faculty of Information Management, 2020)
The study explores a knowledge structure in the weaving culture of the Thai-Khmer ethnic group. Content analysis and a content analysis form were employed to examine the data. The research population was 126 entries from four databases in Thailand, namely, Thai Journal Online (ThaiJO), Thailand Library Integrated System (ThaiLIS), Thailand Culture Research, and Digital Research Information Center (DRIC). As a result, the knowledge structure consists of two classes: 1) textile, including three subclasses and nine divisions (1) yarn preparation; silk threads, coloring, and patterns (2) weaving process; tools and supplies, weaving process, and decoration (3) textile; ikat fabrics and weaving techniques 2) the culture of weaving consists of two subclasses and six divisions (1) ways of life and the use of fabrics including daily use, ceremonial costumes, and traditional costumes (2) beliefs and the fabrics including beliefs through patterns, beliefs through the weaving process, and beliefs in using the fabrics.